Biliary Ascariasis with hepatic abscess in a young boy of 2.5 years of age (Journal of Medicine, 2011)
Ascariasis is the most widespread helminthiasis worldwide. In endemic areas, Ascaris lumbricoides infestation is a very widespread cause of biliopancreatic disease and one of common cause of pancreatitis. Liver abscess as a part of complication of biliary ascariais is possible but not common. Endoscopic management of biliopancreatic ascariasis is feasible, with a very low morbidity and a high rate of success. We experienced a paediatric patient of biliary ascariasis who developed liver abscess as part of complication and initial presentation. Keyword : Helminthiasis, Ascariasis, Hepatic, Abscess DOI: http://dx.doi.org/10.3329/jom.v12i2.6735 JOM 2011; 12(2): 170-173